Crossing Classrooms and Cultures: Filipino Pre-Service Teachers’ SEA Practicum Narratives in Medan, Indonesia (American Journal of Education and Technology, 2025)
Teaching abroad is widely seen as a powerful learning experience, yet stories from the Global South remain underdocumented even though this is where most teachers will eventually practice their craft. In 2025, three ISUFST pre-service teachers took the leap from Iloilo, Philippines, to Medan, Indonesia for SEAMEO’s SEA Teacher Project. They taught English to Grades 5–6, tackled math in gender-segregated classes, and led PE games for high school girls. The month was marked by both nerves and laughter, with lessons that extended well beyond academics. Using a narrative case study approach, evidence from interviews, journals, and teaching artifacts revealed five themes: courage under personal and financial strain; belonging fostered by community hospitality; pedagogy adapted to language barriers; confidence built through reflection and improvisation; and values-driven global citizenship. The findings show that international practicums, when backed with solid support, drive lasting growth. They urge teacher education and policy to move beyond competence, shaping teachers who can lead with resilience and empathy in today’s globalized world.